STUDI KAPASITAS SUNGAI RIAM KIWA MENGGUNAKAN HEC-RAS 4.1.0 - M. Azhari Noor; Budi Utomo (Universitas Lambung Mangkurat, 2013)
South Kalimantan is not spared by the flood. One of the rivers that floods are the river Riam Kiwa. The area being flooded each year is the District Astambul. This research will discuss about the capacity of the river Riam Kiwa Astambul Ruas assisted by HEC-RAS software 4.1.0.The method used is a field research conducted along the river Riam Kiwa Astambul segment, so we get the river Riam Kiwa geometry data were reviewed. The data is then combined with hydrological data so it can do the analysis of hydrology and hydraulics.The research results obtained are flood discharge river Riam Kiwa plans vary for different periods of time. Flood discharge plan increased from 2 years return period flood discharge plan to return period of 100 years. River Riam Kiwa Astambul Ruas could not accommodate due to the capacity of the river is not comparable with the incoming flood discharge. One of the flood control efforts on the river Riam Kiwa Segment Astambul is to build dikes. Embankment required varies for each variation of the flood discharge with return period with a maximum height of 11.0 m embankment. High embankment increases with increasing flood discharge plan.